2017
DOI: 10.18632/oncotarget.23141
|View full text |Cite
|
Sign up to set email alerts
|

17-β-Estradiol induces spreading depression and pain behavior in alert female rats

Abstract: AimsTest the putative contribution of 17-β-estradiol in the development of spreading depression (SD) events and head pain in awake, non-restrained rats.Main MethodsFemale, Sprague-Dawley rats were intact or underwent ovariectomy followed one week later by surgery to place electrodes onto the dura to detect epidural electroencephalographic activity (dEEG). dEEG activity was recorded two days later for 12 hours after systemic administration of 17-β-estradiol (180 μg/kg, i.p.). A separate set of rats were observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 112 publications
1
15
0
1
Order By: Relevance
“…Non-evoked, or pain-suppressed behavior, was also assessed in response to CSD. Previous studies have shown that rearing behaviors are suppressed in response to facial allodynia ( Sandweiss et al, 2017 ; Zhang et al, 2017 ). The ability of cortical KCl to depress rearing behavior was assessed throughout the 72-h behavioral time course.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-evoked, or pain-suppressed behavior, was also assessed in response to CSD. Previous studies have shown that rearing behaviors are suppressed in response to facial allodynia ( Sandweiss et al, 2017 ; Zhang et al, 2017 ). The ability of cortical KCl to depress rearing behavior was assessed throughout the 72-h behavioral time course.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the time of BBB opening corresponded to the peak duration of periorbital allodynia as assessed behaviorally. Non-evoked measures of nociceptive behavior such as rearing have also been used to assess responses in preclinical models of headache ( Sandweiss et al, 2017 ; Zhang et al, 2017 ). Decreases in these non-evoked exploratory behaviors have been suggested to indicate a decrease in quality of life in these animals.…”
Section: Discussionmentioning
confidence: 99%
“…The Dussor research group has developed several models for investigating sex-based differences in progesterone signaling leading to higher incidence of migraines observed in females. An animal model has been developed and utilized by this group to explore the relationship between elevated estrogen levels and specific response patterns to fluctuations of these female sex hormones, further relating to the translational application of progesterone as a treatment [27]. The Dussor and Russo labs have also investigated the differences of CGRP expression in a female model.…”
Section: Preclinical Research Modelsmentioning
confidence: 99%
“…In 2017, Sandweiss et al. published a protocol for inducing migraine-like pain in rodents, in which ovariectomized rats received a single ip bolus of high dose E2 (133). These rats demonstrated decreased exploratory behavior and decreased periorbital pain thresholds.…”
Section: Introductionmentioning
confidence: 99%